Multipoint Background Analysis: Gaining Precision and Accuracy in Microprobe Trace Element Analysis. (12th February 2019) - Allaz, Julien M.; Williams, Michael L.; Jercinovic, Michael J.; Goemann, Karsten; Donovan, John
Abstract: Electron microprobe trace element analysis is a significant challenge. Due to the low net intensity of peak measurements, the accuracy and precision of such analyses relies critically on background measurements, and on the accuracy of any pertinent peak interference corrections. A linear regression between two points selected at appropriate background positions is a classical approach for electron probe microanalysis (EPMA). However, this approach neglects the accurate assessment of background curvature (exponential or polynomial), and the presence of background interferences, a hole in the background, or an absorption edge can dramatically affect the results if underestimated or ignored. The acquisition of a quantitative wavelength-dispersive spectrometry (WDS) scan over the spectral region of interest remains a reasonable option to determine the background intensity and curvature from a fitted regression of background portions of the scan, but this technique can be time consuming and retains an element of subjectivity, as the analyst has to select areas in the scan which appear to represent background. This paper presents a new multi-point background (MPB) method whereby the background intensity is determined from up to 24 background measurements from wavelength positions on either side of analytical lines. This method improves the accuracy and precision of trace element analysis in a complex matrix through careful regression of the background shape, and can be used to characterize the background over a large spectral region covering several elements to be analyzed. The overall efficiency improves as systematic WDS scanning is not required to assess background interferences. The method is less subjective compared to methods that rely on WDS scanning, including selection of two interpolation points based on WDS scans, because "true" backgrounds are selected through an exclusion method of possible erroneous backgrounds. The first validation of the MPB method involves blank testing to ensure the method can accurately measure the absence of an element. The second validation involves the analysis of U-Th-Pb in several monazite reference materials of known isotopic age. The impetus for the MPB method came from efforts to refine EPMA monazite U-Th-Pb dating, where it was recognized that background errors resulting from interference or strong background curvature could result in errors of several tens of millions of years on the calculated date. Results obtained on monazite reference materials using two different microprobes, a Cameca SX-100 Ultrachron and a JEOL JXA-8230, yield excellent agreement with ages obtained by isotopic methods (Thermal Ionization Mass Spectrometry [TIMS], Sensitive High-Resolution Ion MicroProbe [SHRIMP], or Secondary Ion Mass Spectrometry [SIMS]). Finally, the MPB method can be used to model the background over a large spectrometer range to improve the accuracy of background measurement of minor and trace elements acquired on a same spectrometer, a method called the shared background measurement. This latter significantly improves the accuracy of minor and trace element analysis in complex matrices, as demonstrated by the analysis of Rare Earth Elements (REE) in REE-silicates and phosphates and of trace elements in scheelite.